Biological Timekeeping: The Business of a Blind Watchmaker. (June 2016) - Lloyd, David
Fundamental understanding of life depends on both structural and functional details at the molecular level. Continually improving means of measurement of spatial and dynamic properties of biochemical constituents and cellular components complement studies of whole organisms. Integration of the interaction of components to provide coherent behaviour depends on highly elaborate orchestration in space and time. Whereas spatial information on a nanometre resolution is available, and fast dynamic analyses provide biochemical reaction rates measured in nanoseconds, functional coordination of the system requires integrated time dependence. While we are well aware of the special complexity of living organisms, appreciation of temporal scales and their organisation in time is still fragmentary. This article summarises current developments in research on biological time on scales from nanoseconds to years, the networks that connect different time domains and the oscillations, rhythms and biological clocks that coordinate and synchronise the complexity of the living state. "It is the pattern maintained by this homeostasis, which is the touchstone of our personal identity. Our tissues change as we live: the food we eat and the air we breathe become flesh of our flesh, and bone of our bone, and the momentary elements of our flesh and bone pass out of our body every day with our excreta. We are but whirlpools in a river of ever-flowing water. We are not the stuff that abides, but patterns that perpetuate themselves" 60 . Wiener, 1954 "What are called structures are slow processes of long duration, functions are quick processes of short duration" 61 . Von Bertalanffy, 1952